Urgensi Asumsi Filosofis Dalam Menemukan Solusi Atas Problematika Theologi Kristen - Rendi Risky Laowo; Mozes Lawalata (LPPM - STT Kadesi Bogor, 2024)
The problematics of Christian theology are often a point of complex and demanding debate seems to be a very good discussion. Because it is not only a topic of discussion among Christians but is also often an easy terget for liberals. They create and use existing thelogical problems as a tool to attack the Christian faith. That is why it is urgent to take the right steps in responding to this matter. So that this is not allowed to continue and erode the real truth and disrupt the faith of Gods congregation. In seeking solutions to the problems of theological skepticism, a philosophical approach is often a very relevant tool. Philosophical assumptions a deeper understanding of Christian teachings and responding to emerging challenges. So that in this way, all errors and misunderstandings regarding Chrristian theology put forward by liberals can be refuted. Therefore, this article will use qualitative research methods. Methodology with a literature riview approach. The literature review in question is from various writings including books, journals and other literature related to Christian religious education, ontological foundations, epistemology and axiology. Analysis of the subject of discussion is reviwed by reflecting on literature findings with implications for the present. Conclussions are obtained from analytical studies of the theories used. This article will explore the urgency of philosophical assumptions in finding solutions to the problems of Christian theology by referring to several relevant philosophical thoughts. Whit the hope of finding a basis that can help every believer in facing and responding to liberals who want to doubt and attack the Christian faith through a philosophical assumption approach, as a from of apologetics for every believer.